Словник української мови у 20-ти томах як інструмент для створення електронного словника паронімів - Грязнухіна, Т.; Любченко, Т. (Лексикографічний бюлетень, 2011)
The question of the place of paronymy in the automatic text processing has been discussed. A formal description of concepts of the phonetic paronyms and quasiparonyms is given. The principles of automatic building of lexicographical database (LDB) of paronyms have been described. LDB is the basis for creating digital dictionary paronyms. Dictionary article contains information about the types of paronyms (phonetic or quasiparonyms), their grammatical features and about the values of the components of paronymic pair. This information is selected from the Explanatory Dictionary integrated with the LDB of paronyms. Computer technology for creation of digital dictionary of paronyms compiled in the Ukrainian Lingua-Information Fund of National Academy of Sciences of Ukraine has been described.